Geografias das TVs por assinatura na região nordeste : opções tecnológicas e modelos de gestão - Santos, Clécia Carla Silva (2017)
ased upon the lack of studies on the regionalization of communication and telecommunications, this research proposes a mapping of pay-TV in the capitals of the Brazilian Northeast states, analyzing their technological options and theirbusinessmodels.It considers that the restructuring of the State and of capital during the 1990s changed the Brazilian reality, in favor of privatizations opening the market in the telecommunications sector. Under the framework of the Political Economy of Communication and the restricted bibliography on regional communication, this study discusses thetechnological evolutionand the offer of the combined services of Pay-TV in Brazil, addressingfrom the historicalaspects of the normative processes to the determinant regulatory milestones, from Cape Law 8,977 / 95 to Law 12,485 / 2011, which prioritizes the production of national content. The period covered by the dissertation runs from 2012 to 2016, focusing on the Northeast Region, identifying the groups that operate in the segment in the nine Northeastern states,groupedin the following geographic cut: Northern Northeast, which includes the states of Ceará, Piauí and Maranhão; Northeast Central, composed of Pernambuco, Paraíba and Rio Grande do Norte; And the southern Northeast, which covers Bahia, Sergipe and Alagoas.